Where Pentecostalism and Evangelicalism Part Ways: Towards a Theology of Pentecostal Revelatory Experience, Part 1 - Harris, Tania (Asian Journal of Pentecostal Studies, 2020)
The article highlights the Theology of Pentecostal Revelatory Experience. Topics include The ability to hear God's voice is seen by Roger Stronstad to be a distinctive of the New Covenant whereby the Spirit's outpouring at Pentecost enabled all believers to receive revelatory messages in the same manner; Pentecostal experience involves the spontaneous reception of revelation apart from cognitive thought, and comprises a genuine transfer of new and/or previously unknown information.